Predictors of Outcome in Conservative and Minimally Invasive Surgical Management of Pain Originating From the Sacroiliac Joint: A Pooled Analysis. Issue 21 (1st November 2017) - Dengler, Julius; Duhon, Bradley; Whang, Peter; Frank, Clay; Glaser, John; Sturesson, Bengt; Garfin, Steven; Cher, Daniel; Rendahl, Aaron; Polly, David
Abstract : Study Design: A pooled patient-level analysis of two multicenter randomized controlled trials and one multicenter single-arm prospective trial. Objective: The aim of this study was to identify predictors of outcome of conservative and minimally invasive surgical management of pain originating from the sacroiliac joint (SIJ). Summary of Background Data: Three recently published prospective trials have shown that minimally invasive SIJ fusion (SIJF) using triangular titanium implants produces better outcomes than conservative management for patients with pain originating from the SIJ. Due to limitations in individual trial sample size, analyses of predictors of treatment outcome were not conducted. Methods: We pooled individual patient data from the three trials and used random effects models with multivariate regression analysis to identify predictors for treatment outcome separately for conservative and minimally invasive surgical treatment. Outcome was measured using visual analogue scale (VAS), Oswestry Disability Index (ODI), and EuroQOL-5D (EQ-5D). Results: We included 423 patients assigned to either nonsurgical management (NSM, n = 97) or SIJF (n = 326) between 2013 and 2015. The reduction in SIJ pain was 37.9 points larger [95% confidence interval (95% CI) 32.5–43.4, P  < 0.0001] in the SIJF group than in the NSM group. Similarly, the improvement in ODI was 18.3 points larger (95% CI 14.3–22.4), P  < 0.0001). In NSM, we found no predictors of outcome. In SIJF, a reduced improvement in outcome was predicted by smoking ( P  = 0.030), opioid use ( P  = 0.017), lower patient age ( P  = 0.008), and lower duration of SIJ pain ( P  = 0.028). Conclusions: Our results support the view that SIJF leads to better treatment outcome than conservative management of SIJ pain and that a higher margin of improvement can be predicted in nonsmokers, nonopioid users, and patients of increased age and with longer pain duration. Level of Evidence: 1